Analysis of the Role of Social Media in Shaping Public Opinion on Social Issues - Hasanuddin, Muhammad; Khodijah, Siti; Rizki, Cindy Atika (Journal of Computer Science, Artificial Intelligence and Communications, 2024)
This research aims to analyze the role of social media in shaping public opinion on social issues that are developing in society. Social media has become the main platform for the dissemination of information and public communication, replacing the traditional role of mass media in shaping public perception. This research uses a qualitative approach with literature study methods and observation of public interactions on various social media platforms such as Twitter, Instagram, and Facebook. The research results show that social media has a significant influence in shaping public opinion, especially through content virality, the role of influencers, and algorithmic mechanisms that reinforce echo chambers. Social issues such as gender equality, the environment, and social justice become active discussion topics and are capable of creating digital social movements. However, the role of social media also brings challenges such as the spread of misinformation and opinion polarization. Thus, a deeper understanding of social media dynamics becomes important for the healthy and constructive management of public issues. This research is expected to contribute to the development of more effective social communication strategies in the digital era